Determiners of fast-food consumption in Iranian university students: Application of prototype/willingness model - Seyed Saeed Mazloomy Mahmoodabad; Mahmood Mahbobirad; Mohammad Asadpour; Ali Akbar Vaezi; Hossein Fallahzadeh; Hassan Zareei Mahmoodabadi (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Today, marked by advanced scientific approach, urbanism, and changing life style, there is an ever-growing rate of fast-food consumption, which has significantly affected public health. Hence, the present research aimed to predict factors involved in fast-food consumption in light of the prototype/willingness model among the students of Rafsanjan University of Medical Sciences. MATERIALS AND METHODS: In the present descriptive/analytical research conducted in 2018-2019, 350 students in Rafsanjan University of Medical Sciences were selected through proportionate stratified random sampling. The required data were collected using a self-administrated questionnaire in light of the constructs within the prototype/willingness model and fast-food consumption behavior. The data were analyzed in SPSS version 16.0 using descriptive and inferential statistics including mean scores, standard deviation, correlation coefficient, and linear regression. RESULTS: Behavioral intention of fast-food consumption showed to be positively correlated with positive willingness, positive prototype, positive subjective norms, and positive attitude toward fast-food consumption. Furthermore, the correlation between positive behavioral intention of consuming fast food and positive subjective norms and positive attitude toward fast-food consumption was statistically significant (P < 0.05). The underlying constructs of prototype/willingness model altogether managed to explain 13% of the total variance of fast-food consumption behavior. Behavioral intention showed to be the strongest predictor of the behavior (β = 1.613). CONCLUSION: It is suggested that the preventive measures aimed to reduce fast-food consumption among the youth focus more on strengthening negative attitudes and subjective norms concerning fast-food consumption.